2018
DOI: 10.1016/j.msea.2018.01.061
|View full text |Cite
|
Sign up to set email alerts
|

Structure and hardness of B2 ordered refractory AlNbTiVZr0.5 high entropy alloy after high-pressure torsion

Abstract: High-pressure torsion (HPT) at room temperature was applied to an AlNbTiVZr 0.5 refractory high entropy alloy. In the initial as-cast condition the alloy was composed of a coarse-grained B2 matrix phase and a continuous network of C14 Laves phase particles with the volume fraction of 19%. HPT resulted in the formation of a nanocrystalline structure in the B2 matrix with an average size of grains/subgrains of 25 nm after 5 revolutions. The B2 phase also underwent significant disordering during HPT. The Laves ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(10 citation statements)
references
References 57 publications
0
10
0
Order By: Relevance
“…Therefore, the lattice distortion is not expected to be high in any possible atomic pair. However, the shear modulus of Cr (110 GPa) is noticeably higher than that for the other elements (38)(39)(40)(41)(42)(43)(44)(45)(46)(47). Therefore, strong modulus distortions are expected around Cr atoms that can generate the strongest solid solution strengthening.…”
Section: Tablementioning
confidence: 97%
See 1 more Smart Citation
“…Therefore, the lattice distortion is not expected to be high in any possible atomic pair. However, the shear modulus of Cr (110 GPa) is noticeably higher than that for the other elements (38)(39)(40)(41)(42)(43)(44)(45)(46)(47). Therefore, strong modulus distortions are expected around Cr atoms that can generate the strongest solid solution strengthening.…”
Section: Tablementioning
confidence: 97%
“…This approach has been used extensively for HEAs based on late 3d transition metals [28][29][30][31][32][33][34][35], but not often applied to RHEAs/RCCAs [36]. In this work, microstructure and microhardness evolution during cold rolling and subsequent annealing at 800-1200°C of a new non-equiatomic Ti-Cr-Nb-V (Ti 1.89 CrNbV 0.56 ) RHEA, developed on the basis of earlier results on the Al-Cr-Nb-Ti-V-Zr system RHEAs/RCCAs [7,8,13,[37][38][39][40][41][42][43], are studied in details.…”
Section: Introductionmentioning
confidence: 99%
“…The B2 phase is often observed in alloys with Al [19][20][21][22][23]. Some alloys were revealed to have a single B2 phase structure [20,23,24], sometimes containing a small amount of non-coherent secondary phases like a Laves phase, σ-phase or Zr aluminides [25,26]. However the most attractive option is probably associated with the production of a mixture of the bcc þ B2 coherent phases.…”
Section: Introductionmentioning
confidence: 99%
“…An abundance of investigations have emerged in the literature focusing on microstructural characteristics, defect evolution as well as mechanical properties for HEAs after SPD. [99][100][101][102][103][104][105][106][107][108][109] A recent work by Bhattacharjee et al 106 reported that the nanolamellar AlCoCrFeNi 2.1 HEA, which was achieved by cryorolling and annealing processes, exhibited a remarkable increase in both the yield strength and the ultimate tensile strength (UTS) without sacrificing too much ductility [ Fig. 8(a)].…”
Section: Grain Coarseningmentioning
confidence: 99%